Plants on Plants - The Biology of Vascular Epiphytes - Zotz, Gerhard (Fascinating Life Sciences,, 2016)
This book critically reviews advances in our understanding of the biology of vascular epiphytes since Andreas Schimper's 1888 seminal work. It addresses all aspects of their biology, from anatomy and physiology to ecology and evolution, in the context of general biological principles. By comparing epiphytes with non-epiphytes throughout, it offers a valuable resource for researchers who are not primarily interested in this plant group. A particular strength is the identification of research areas that have not received the attention they deserve, with conservation being a case in point. Scientists have tended to study pristine systems, but global developments call for information on epiphytes in human-disturbed systems and the response of epiphytes to global climate change.